Economic Growth and Pollutant Emissions: New Panel Evidence from the Union for the Mediterranean Countries - Mouna Ben Abdeljelil; Christophe Rault; Fateh Belaïd (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates the existence of an environmental Kuznets curve (EKC) and its robustness for 28 countries of the Union for the Mediterranean (UfM) over the recent period. Our methodology relies on four recent estimation methods for non-stationary panel data and includes four pollutants (two global and two local). Two main results emerge from our analysis. First, the EKC does not hold for most pollutants, and its validity crucially depends on the estimation techniques considered. Second, the Pooled-Mean Group method is the most favourable one and confirms the existence of an inverted U-shaped relationship for CO2 and SO2. Our results provide beneficial information for decision-makers. They suggest implementing proactive instruments based on both flexible regulations and tax incentives to stimulate ecological transition.
Keywords: O44; Q53; R58; 330; environmental Kuznets curve; pollution; regional integration; The Union for the Mediterranean